O comportamento de compra dos consumidores de Santo Antônio do Planalto no varejo físico e virtual - Bueno, Kymberli Damaris Freitas (2023)
The present work aims to analyze the consumer behavior in the municipality of Santo Antônio do Planalto. Regarding the theoretical framework, the theories used in this work were based on informing the importance of consumer behavior, identifying determining factors and making clearer the vision of those who wish to undertake business in the city. It was based on the understanding of consumer behavior, buying behavior, retail management, physical and online retailing, and digital marketing. The data was collected by means of a questionnaire applied to a sample of about 100 people residing in the town. A descriptive analysis was carried out, to the data arising from the quantitative approach, aiming to determine the preferences of the population in relation to their shopping options.